2007
DOI: 10.1111/j.1600-079x.2007.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

The co‐catalytic effect of chlorpromazine on peroxidase‐mediated oxidation of melatonin: enhanced production of N1‐acetyl‐N2‐formyl‐5‐methoxykynuramine

Abstract: Accumulating evidence points to relationships between increased production of reactive oxygen or decreased antioxidant protection in schizophrenic patients. Chlorpromazine (CPZ), which remains a benchmark treatment for people with schizophrenia, has been described as a pro-oxidant compound. Because the antioxidant compound melatonin exerts protective effects against CPZ-induced liver disease in rats, in this investigation, our main objective was to study the effect of CPZ as a co-catalyst of peroxidase-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…As previously reported, CPZ, an efficient substrate of peroxidase, is oxidized to CPZ •+ , which acts as a co‐catalyst during the oxidation of melatonin [23]. Here, the pH and buffer identity studies were performed using 100 μ m of CPZ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously reported, CPZ, an efficient substrate of peroxidase, is oxidized to CPZ •+ , which acts as a co‐catalyst during the oxidation of melatonin [23]. Here, the pH and buffer identity studies were performed using 100 μ m of CPZ.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that the pH of the reaction medium and the addition of CPZ could exacerbate the efficiency of AFMK production during the peroxidasecatalyzed oxidation of melatonin [23,24]. As there is an increasing demand for AFMK, here we screened for an optimized procedure for the preparation of this compound.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that CPZ is a dopamine-receptor antagonist antipsychotic agent (6). CPZ, which remains a benchmark treatment for individuals with schizophrenia, has been described as a prooxidant compound (7). Moreover, CPZ is a phenothiazine derivative used clinically to control psychotic disorders, and has been found to exhibit anticancer activity (8).…”
Section: Introductionmentioning
confidence: 99%